Optimizar la convivencia en las instituciones educativas - García-Vidal, Marcos (2019)
Coexistence is neither a unitary nor a static concept; rather, it is a collective and dynamic construction, subject to change as the interrelationships among the actors involved evolve over time. This entails a fundamental implication: coexistence is not the individual responsibility of any single actor, but of the entire educational community as a whole. Therefore, promoting democratic learning that fosters dialogue among individuals, mutual support, and cooperation—learning that seeks to create spaces for sharing interests, concerns, and aspirations, where individuals can both offer and request assistance, and that includes all members in the development of group norms—is one of the ongoing tasks we face in order to cultivate environments conducive to positive coexistence.